2019
DOI: 10.1016/j.dib.2019.103829
|View full text |Cite
|
Sign up to set email alerts
|

Potential of cereal-based agricultural residues available for bioenergy production

Abstract: This data article ranks 294 countries worldwide with more potential available, of cereal based agricultural residues for bioenergy production. Nine different cereal-based agricultural waste products (barley, wheat, millet, oat, rice, and rye straw, sorghum straw/stalk, and maize cob) are used. The tables and figures are grouped by the most prevalent Köppen-Geiger climate classification (tropical/megathermal, dry (desert and semi-arid), temperate/mesothermal, continental/microthermal), continent and region. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Although Nigeria has been reported as an emerging economy for biofuel production [37], a study by Rocha-Meneses et al [38] shows that the country is only 19th out of 27 in the equatorial Africa with more potential available for bioenergy production. The study reported the utilization of agricultural waste as barley, wheat, millet, oat, rice, rye, sorghum, and maize for bioenergy production.…”
Section: Napier Grass Availability Production and Growthmentioning
confidence: 99%
“…Although Nigeria has been reported as an emerging economy for biofuel production [37], a study by Rocha-Meneses et al [38] shows that the country is only 19th out of 27 in the equatorial Africa with more potential available for bioenergy production. The study reported the utilization of agricultural waste as barley, wheat, millet, oat, rice, rye, sorghum, and maize for bioenergy production.…”
Section: Napier Grass Availability Production and Growthmentioning
confidence: 99%
“…According to Statistics Estonia [9], the area for barley cultivation in Estonia was in the range of 102,487 to 138,485 ha for the last 5 years (2016-2020). Roughly around 2.79 tons of straw can be produce per ha of barley cultivation [10]. Thus, the potential for barley straw production in Estonia is around 285,000 tons for the last 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…The milk production in this region has grown by 42% in the last two decades (Fariña et al., 2020). In the countries where SB is not available, other kinds of lignocellulosic material could be used (Rocha‐Meneses et al., 2019). For this reason, further studies testing different lignocellulosic material as dairy fatty waste adsorbents should be performed.…”
Section: Resultsmentioning
confidence: 99%